Sonic environment and vegetation structure: A methodological approach for a soundscape analysis of a Mediterranean maqui (Ecological InformaticsEcological Informatics, 2014)
Herein we present one of the first attempts to couple the complexity of vegetation and topographic features with the sonic environment to understand the distribution of bird species and individuals in their habitat. To achieve this, the sonic features of a bird community were studied during the spring and early summer of 2011 in a Mediterranean maqui located on the western slope of a remote hanging valley that is dominated by Erica arborea, Quercus ilex and Arbutus unedo. Species composition, height, vertical foliage profile, canopy density and dispersion of vegetation were utilized as probable proxies for the sonic patterns. The acoustic activity of birds was collected through the use of a regular matrix of 20 audio recorders, spaced 25m apart, which were placed following the topographic isoclines. The sonic complexity of the soundscape was evaluated using the Acoustic Complexity Index (ACI), which is a recently developed metric. The PCA applied to the vegetation parameters revealed two principal distinguishing factors, which we were able to define as “vegetation density and structure” and “species segregation.” Moreover, the results show that, even in the case of sampling sites that are very close together, sonic patterns vary across the season, highlighting the great variability of the soundscape and confirming the adequacy of the sampling scale of 25m adopted in this study. The topographic features do not seem to be connected to the sonic environment. The main sonic complexity was found where the vegetation was taller and denser, especially where E. arborea was the dominant species. Although this proves that acoustic dynamics can be linked to vegetation structure, even on a small scale, a consistent element of sonic variability cannot be explained by vegetation patterns alone, and a soundtope hypothesis must be invoked.

Landscape structure and breeding bird distribution in a sub-Mediterranean agro-ecosystem - Farina, Almo (Landscape Ecology, 1997)
Richness, abundance and distribution of birds were investigated in the Aulella watershed, a mountainous area of 300 km2 , located in the extreme northwestern corner of Tuscany, Italy in spring and summer, 1995. The study area encompasses five vegetation types (from Mediterranean maqui to upland beech forest) and three main land use categories (woodlands, mixed cultivated + urban areas, montane prairies). The recent history of land abandonment in the study area has produced a rapid expansion of shrubland and woodland, reducing cultivated areas to small patches interspersed in a woodland matrix. Richness, abundance and distribution of birds recorded at 414 points, randomly selected along secondary roads, and located using a Global Positioning System (GPS), were compared with topography, vegetation type and land use in a Geographic Information Systems (GIS) with a grid cell resolution of 200 × 200 m. Bird richness (55 species in all) and abundance are correlated: (a) negatively with the increasing altitude and increasing distance from cultivated areas; (b) positively with the increasing distance from woodlands and mountain prairies. Slope orientation appears to have a negligible effect on bird assemblages. Bird richness and abundance are significantly correlated with vegetation type. Cultivated areas support the highest bird richness and abundance that increase with patch size of the cultivated areas. Local extinction and/or reduction in within-species abundance of birds are expected to continue if the process of land abandonment continues.
Keywords: aulella watershed; geographic information systems; global positioning system; sub-mediterranean agro-ecosystem; tuscany

Landscape structure and breeding bird distribution in a sub-Mediterranean agro-ecosystem (Landscape Ecology, 1997)
Richness, abundance and distribution of birds were investigated in the Aulella watershed, a mountainous area of 300 km2 , located in the extreme northwestern corner of Tuscany, Italy in spring and summer, 1995. The study area encompasses five vegetation types (from Mediterranean maqui to upland beech forest) and three main land use categories (woodlands, mixed cultivated + urban areas, montane prairies). The recent history of land abandonment in the study area has produced a rapid expansion of shrubland and woodland, reducing cultivated areas to small patches interspersed in a woodland matrix. Richness, abundance and distribution of birds recorded at 414 points, randomly selected along secondary roads, and located using a Global Positioning System (GPS), were compared with topography, vegetation type and land use in a Geographic Information Systems (GIS) with a grid cell resolution of 200 × 200 m. Bird richness (55 species in all) and abundance are correlated: (a) negatively with the increasing altitude and increasing distance from cultivated areas; (b) positively with the increasing distance from woodlands and mountain prairies. Slope orientation appears to have a negligible effect on bird assemblages. Bird richness and abundance are significantly correlated with vegetation type. Cultivated areas support the highest bird richness and abundance that increase with patch size of the cultivated areas. Local extinction and/or reduction in within-species abundance of birds are expected to continue if the process of land abandonment continues.